Clinical and Radioraphic Study to Compaer Between Mineral Trioxide Aggregate (MTA) and Platelet‑Rich Fibrin Membranes (PRF) in Management of Immatuer Permanent Teeth with Pulpitis (Journal of Hama University, 2020)
Aim: The aim of this study was to compare Between the application of Mineral Trioxide aggregate (MTA) alone or combination with platelet-rich fibrin (PRF) as a partial pulpotomy agent in immature permenant teeth with pulpits.Material and Methods: In this study, 20 immature permenant teeth from 20 healthy patient aged 6-12 years with pulpits were randomly divided into two groups. 1) First group (n=10): after caries excavation, removal of 1-2 mm of pulp, and hemostasis, the exposed pulp was covered with PRF membrane then a layer of mineral trioxide aggregate cement (MTA) was applied. 2) Second group (n=10): after caries excavation, removal of 1-2 mm of pulp, and hemostasis, the exposed pulp was covered with MTA. All teeth were restored with glass -ionomer cement and composite resin. Clinical and radioraphic evaluation was undertaken at (3, 6, and 12) months intervals. The results were analyzed using appropriate statistical tests.Results: The results of current study showed that all the teeth in both groups were asymptomatic and responded positively to the electrical pulp test during all follow-up periods. Radiographic examination showed dentinal bridge formation and continued root development in both groups but the response was faster in (MTA + PRF) group.Conclusion: Clinical and radiological findings showed that PRF membranes used for partial pulpotomy in permenant teeth with pulpits can improve treatment pargnosis, but it needs  more study with follow-up with longer recall periods and additional clinical variables.